Microglial activation in spaceflight and microgravity: potential risk of cognitive dysfunction and poor neural health - Li, Zihan; Wu, Jiarui; Zhao, Tianyuan; Wei, Yiyun; Xu, Yajing; Liu, Zongjian; Li, Xiaoqiong; Chen, Xuechai (Frontiers in Cellular Neuroscience, 2024)
Due to the increased crewed spaceflights in recent years, it is vital to understand how the space environment affects human health. A lack of gravitational force is known to risk multiple physiological functions of astronauts, particularly damage to the central nervous system (CNS). As innate immune cells of the CNS, microglia can transition from a quiescent state to a pathological state, releasing pro-inflammatory cytokines that contribute to neuroinflammation. There are reports indicating that microglia can be activated by simulating microgravity or exposure to galactic cosmic rays (GCR). Consequently, microglia may play a role in the development of neuroinflammation during spaceflight. Prolonged spaceflight sessions raise concerns about the chronic activation of microglia, which could give rise to various neurological disorders, posing concealed risks to the neural health of astronauts. This review summarizes the risks associated with neural health owing to microglial activation and explores the stressors that trigger microglial activation in the space environment. These stressors include GCR, microgravity, and exposure to isolation and stress. Of particular focus is the activation of microglia under microgravity conditions, along with the proposal of a potential mechanism.